Penyusunan Anggaran Discretionary Expenses pada PT Anshun Joyful T & T - Irsutami Irsutami; Printasani Debby Wulan (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2014)
The final research was conducted at PT Anshun Joyful T & T Batam (PT AJTT). The problem faced by the PT AJTT is how budgeting discretionary expenses, for the purposes set out is to develop a budget that is discretionary. Data collection techniques used were interviews and observation data were analyzed descriptively. Conclusions from this research that the drafting of the discretionary budget that PT AJTT that can be used to control discretionary costs.